Effects of different core exercises on respiratory parameters and abdominal strength - Cavaggioni, Luca (J Phys Ther Sci, 2015)
[Purpose] This study determined the effects a new modality of core stabilization exercises based on diaphragmatic breathing on pulmonary function, abdominal fitness, and movement efficiency. [Subjects] Thirty-two physically active, healthy males were randomly assigned to an experimental group (n = 16) and a control group (n = 16). [Methods] The experimental group combined diaphragmatic breathing exercises with global stretching postures, and the control group performed common abdominal exercises (e.g., crunch, plank, sit-up), both for 15 minutes twice weekly for 6 weeks. Pulmonary function (measured by forced vital capacity, forced expiratory volume in 1 second, and peak expiratory flow) and abdominal fitness (measured with the American College of Sports Medicine curl-up [cadence] test and the Functional Movement Screen(TM)) were evaluated before and after the intervention. [Results] Significant changes in curl-up (cadence) test scores, Functional Movement Screen scores, and all pulmonary parameters were recorded in the experimental group at the posttraining assessment, whereas in the control group, no significant differences over baseline were observed in any parameters. [Conclusion] Compared with traditional abdominal exercises, core stabilization exercises based on breathing and global stretching postures are more effective in improving pulmonary function and abdominal fitness.